Postpartum contraceptive practices among urban and peri-urban women in North India: a mixed-methods cohort study protocol - Roy, Nivedita; Adhikary, Priyanka; Kabra, Rita; Kiarie, James; Mburu, Gitau; Dhabhai, Neeta; Chowdhury, Ranadip; Mazumder, Sarmila (BMC pregnancy and childbirth, 2021)
Background Postpartum family planning (PPFP) helps women space childbirths, increase exclusive breastfeeding and prevent unintended pregnancies, leading to reduction in maternal, infant and child morbidities and mortality. Unmet need of family planning is highest among women in the postpartum period due to lack of knowledge, cultural and religious barriers, access barriers and low antenatal care service utilization. However, in spite of low prevalence of postpartum family planning practices, birth-to-birth interval is reportedly high in Delhi, India. This study explores the postpartum contraception practices and the relationship between use of postpartum contraception and subsequent child linear growth. Methods This is a mixed method cohort study on PPFP and is nested within an ongoing “Women and Infants Integrated Interventions for Growth Study” (WINGS). Married women aged 18–30 years who have delivered a live baby are recruited for quantitative interviews at 6 weeks, 6, 12, and 24 months postpartum. In-depth interviews are conducted with a randomly selected sub-sample of women at each of the four time points, 35 husbands and 20 local service providers to understand their perspectives on PPFP practices. Discussion The findings from the study will provide useful insights into couples’ contraception preferences and choice of contraception, modern and traditional, initiation time and the effect of birth spacing and contraception use on subsequent linear growth of the child. This knowledge will be of significant public health relevance and will help in designing appropriate interventions for appropriate postpartum contraception use and delivery strategies. The study aims to work address the Sexual and Reproductive Health and Rights goal of promoting reproductive health, voluntary and safe sexual and reproductive choices for women. Trial registration Trial registration number: CTRI/2020/03/023954 .